Akad kafalah, kafalah bil ujrah dan hawalah prespektif fiqih, KHES dan Fatwa DSN-MUI - Junaidi, Ahmad Khusnan (Maliki Interdisciplinary Journal, 2024)
This review examines “Kafalah Contracts, Kafalah bil Ujrah (kafalah combined with ijarah contracts) and Hawalah” in the perspective of Fiqh (Islamic Law), KHES (Sharia Economic Financing) and DSN-MUI Fatwa (National Sharia Council).. This study applies a qualitative normative approach to analyze the combination of kafalah (guarantee) and ijarah (lease) contracts in the context of Islamic finance. The results of the analysis show that the merging of kafalah and ijarah contracts to become kafalah bil ujrah creates an Islamic financial model that is more flexible and consistent with the principles of Islamic law. In addition, this study also explains the concept of hawalah (transfer of debt) in the context of kafalah bil ujrah. This approach reflects efforts to integrate sharia values into modern financial practices and provides clear legal guidelines based on the DSN-MUI Fatwa.